The role of hospital dentistry and neurology in the conjoined treatment and diagnosis of neuropathies: a case report - Neri, Pedro; Carvalho, Pedro Rubens Araujo; Matos, Lucas Adeilson dos Santos; Ramalho, Erika Queiroga; Silva, Francisco Willame da; Santos, Eliardo Silveira; Silva, Carla Welch da; Parente, Enzo Lima Alcântara; Costa, Rafaella Iughetti da; Nogueira, João Vítor Moreira (Headache Medicine, 2024)
Introduction: Neuropathic pain is an algic syndrome resulting from lesion, disease or dysfunction in the central and/or peripheral nervous system and can be associated with invasive dental procedures. Objective: Report the conjoined role of Hospital Dentistry (HD) and Neurology in the diagnosis and treatment of a patient with peripheral neuropathy (PN). Case report: 67-year-old female diagnosed with trigeminal neuralgia (TN) was referred from a service external to the Neurology ambulatory of Fortaleza’s General Hospital- SESA to be evaluated by the HD team, with recommendation of extirpating the inferior alveolar nerve due to the failure of many drug therapies. During the clinical examination, the patient referred to acute and persistent pain in the middle and inferior thirds on the right side of the face which started after an endodontic procedure. In the oral cavity the patient presented bimaxillary partial edentulism, inferior alveolar ridge with signs of resorption and knife edge pattern. Therefore, the PN hypothesis was considered and a new therapeutic protocol was suggested. The management was based on the switch of medication by the doctor team associated with photobiomodulation performed by the HD team. To measure the pain level the Visual Analogue Scale (VSA) was used each session, which made it possible to observe the expressive reduction in symptomatology, reducing the score from 9 to 3 at the end of the second protocol. Conclusion: The interdisciplinary cooperation between the HD and neurology teams made the correct diagnosis and treatment possible, managing pain and improving life quality through conservative therapy.